Exploring the causal association between epigenetic clocks and menopause age: insights from a bidirectional Mendelian randomization study - Wang, Ling; Xu, Shuling; Chen, Rumeng; Ding, Yining; Liu, Menghua; Hou, Chunyan; Wu, Zhu; Men, Xiaoju; Bao, Meihua; He, Binsheng; Li, Sen (Frontiers in Endocrinology, 2024)
Background: Evidence suggests a connection between DNA methylation (DNAm) aging and reproductive aging. However, the causal relationship between DNAm and age at menopause remains uncertain. Methods: Employing established DNAm epigenetic clocks, such as DNAm Hannum age acceleration (Hannum), Intrinsic epigenetic age acceleration (IEAA), DNAm-estimated granulocyte proportions (Gran), DNAm GrimAge acceleration (GrimAgeAccel), DNAm PhenoAge acceleration (PhenoAgeAccel), and DNAm-estimated plasminogen activator inhibitor-1 levels (DNAmPAIadjAge), a bidirectional Mendelian randomization (MR) study was carried out to explore the potential causality between DNAm and menopausal age. The primary analytical method used was the inverse variance weighted (IVW) estimation model, supplemented by various other estimation techniques. Results: DNAm aging acceleration or deceleration, as indicated by Hannum, IEAA, Gran, GrimAgeAccel, PhenoAgeAccel, and DNAmPAIadjAge, did not exhibit a statistically significant causal effect on menopausal age according to forward MR analysis. However, there was a suggestive positive causal association between DNAm estimated granulocyte levels and age at menopause (Beta = 0.0010; 95% confidence interval (CI): 0.0004, 0.0020) in reverse MR analysis. Conclusion: The observed increase in granulocyte DNAm levels in the blood in relation to menopausal age could potentially serve as a valuable indicator for evaluating the physiological status at the onset of menopause.